Desenvolvimento de uma família de reatores eletrônicos para lâmpadas fluorescentes sem eletrodos empregando a técnica de integração de conversores - Silva, Marcelo Freitas da (2012)
This paper presents the design and development of an electronic ballasts family obtained through the use of the integration technique of converters for feeding the electrodeless fluorescents lamps (EFL). This type of lamp is driven by electromagnetic effects and because of this the electrodes are eliminated. Thus, the EFL has longer lifetime associated with low lumen depreciation representing an alternative to lighting systems among other discharge lamps. It is necessary to develop an electrical model capable of describing the behavior of the lamp in order to design electronic circuits to provide a good operation. In this work, the developed model includes not only, the lamp static behavior at different operating points, but also the magnetic losses involved. Because of the EFL magnetic characteristics, the operation frequency of this type of system has to be high in order to reduce the size of inductive elements avoiding the glare. Due to this, it is proposed a set of electronic systems for feeding the lamp in an efficient way. The systems are studied to establish relationships regarding the behavior and limitations imposed by them. This work also presents the power control delivered to the lamp. Finally, experimental results are presented in order to validate the developed project.